Affective communication in Kathakali performance / Vishnu Achutha Menon and N Boobalakrishnan - Menon, Vishnu Achutha; Natrayan, Boobalakrishnan (Faculty of Art and Design, 2024)
This study delves into investigating the extent of individual differences in expressiveness among Kathakali actors participating in the Red Beard Festival. The research employs Howard S. Friedman's Affective Communication Test (ACT), a self-report measure specifically designed to assess variations in individual expressiveness among Kathakali actors. The study selected 33 Kathakali actors who took part in the Red Beard Festival of Kathakali in 2021, utilising a purposive sampling method to gather participants. The Affective Communication Test (ACT) was administered to the selected participants, and a quantitative analysis was conducted to analyse the data. The descriptive measures were employed to obtain the socio-demographic profile of the participants. The results of the study revealed a range of scores on the Affective Communication Test (ACT) between 70 and 117, with a mean score of 111.55 and a standard deviation of ± 1.46. The inferential statistical analysis demonstrated no significant differences in individual expressiveness among the participants in relation to gender, age, educational qualification, occupation, or marital status. Moreover, correlation analysis revealed that neither the number of years of training nor the years of experience had a significant impact on individual expressiveness.